(untitled) (London, 2013)
The visual history of the American West calls to mind iconic artworks and nostalgia for the past. Art of the American Frontier presents more than 300 artworks and artifacts from 1830 to 1930, alongside a group of contemporary Western works, showcasing the premier collections of the Buffalo Bill Center of the West. The complicated history of westward expansion is presented through the iconography of the frontier, spanning Plains Indian materials, government survey photographs, and paintings by early artist-explorers. In the 20th century, a growing romance with the West is evident in the theatrics of Buffalo Bill Cody and his Wild West show, with its blend of popular culture and history that inspired numerous artists.
Keywords: Nghệ thuật, mỹ,Art, American; Triển lãm,Exhibitions; Thế kỷ 20,20th century -; Tây (Hoa Kỳ),West (U.S.)